Tuberous sclerosis in pregnancy: a rare genetic disease requiring multidisciplinary approach in pregnancy - Madan, Shikha; Kumar, Pardeep; Anand, Smriti; Singhal, Savita; Sangwan, Neetu; Dalal, Monika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Tuberous sclerosis complex (TSC) is a multisystemic, autosomal dominant genetic disorder with complete penetrance, that can evolve with hamartomas in multiple organs, such as skin, central nervous system, kidney and lung. Penetrance in genetics is the proportion of individuals carrying a particular variant (or allele) of a gene (the genotype) that also express an associated trait (the phenotype). Due to the wide phenotypic variability in TSC, the disease is often not recognized. The diagnostic criteria for tuberous sclerosis were reviewed in 2012, at the second International tuberous sclerosis complex consensus conference. The diagnosis is based on genetic criteria, by the identification of inactivating pathogenic mutation of tumour suppressor genes TSC1 and TSC2, and clinical criteria, including cutaneous, renal, pulmonary, cardiac and neurological manifestations. Authors present with a rare case report of a patient with TSC presenting at term.